Substance-Specific Differences in Human Electroencephalographic Burst Suppression Patterns - Fleischmann, Antonia; Pilge, Stefanie; Kiel, Tobias; Kratzer, Stephan; Schneider, Gerhard; Kreuzer, Matthias (Frontiers in Human Neuroscience, 2018)
Different anesthetic agents induce burst suppression in the EEG at very deep levels of general anesthesia. EEG burst suppression has been identified to be a risk factor for postoperative delirium. EEG based automated detection algorithms are used to detect burst suppression patterns during general anesthesia and a burst suppression ratio is calculated. Unfortunately, applied algorithms do not give information as precisely as suggested, often resulting in an underestimation of the patients’ burst suppression level. Additional knowledge of substance-specific burst suppression patterns could be of great importance to improve the ability of EEG based monitors to detect burst suppression. In a re-analysis of EEG recordings obtained from a previous study, we analyzed EEG data of 45 patients undergoing elective surgery under general anesthesia. The patients were anesthetized with sevoflurane, isoflurane or propofol (n=15, for each group). After skin incision, the used agent was titrated to a level when burst suppression occurred. In a visual analysis of the EEG, blinded to the used anesthetic agent, we included the first distinct burst in our analysis. To avoid bias through changing EEG dynamics throughout the burst, we only focused on the first 2s of the burst. These episodes were analyzed using the absolute and relative power spectral density, the absolute burst amplitude and absolute burst slope, as well as permutation entropy. Our results show significant substance-specific differences in the architecture of the burst. Volatile-induced bursts showed higher burst amplitudes and higher burst power. Propofol-induced bursts had significantly higher relative power in the EEG alpha-range. Further, isoflurane-induced bursts had the steepest burst slopes. We can present the first systematic comparison of substance-specific burst characteristics during anesthesia. Previous observations, mostly derived from animal studies, pointing out the substance-specific differences in bursting behavior, concur with our findings. Our findings of substance-specific EEG characteristics can provide information to help improve automated burst suppression detection in monitoring devices. More specific detection of burst suppression may be helpful to reduce excessive EEG effects of anesthesia and therefore the incidence of adverse outcomes such as postoperative delirium.